Analysis of Student Organization Management Conflict:Case Study of the Appointment of Acting Regional Administrators of KAMMI Medan and Deli Serdang - Andriarta, Thio; Azim, Fauzan; Hasibuan, Mhd Ali; Ramadhan, Bayu; Azura, Nazua; Hasibuan, Nuraini (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Internal conflict is an inseparable phenomenon from organizational dynamics, including student organizations that have complex structures, ideologies, and leadership mechanisms. The conflict within the Indonesian Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI) at the Medan and Deli Serdang Regional Board levels reflects tensions between structural legitimacy and personal interests, triggered by indications of violations of the organization's khittah (basic principles) and the emergence of dual loyalty among administrators. Objective: This article aims to analyze the leadership conflict within KAMMI Medan and Deli Serdang, particularly focusing on the appointment of an Acting Leader (Plt.) by the Central Board as a form of structural conflict management. Method: This research employs a literature study method with a qualitative-descriptive approach. Findings and Implications: The findings indicate that unmanaged conflict has the potential to cause organizational dysfunction, reduce cadre trust, and hinder the cadre development process. The appointment of an Acting Leader by the Central Board represents a structural conflict management strategy aimed at maintaining organizational stability and restoring the legitimacy of regional management. This study contributes academically to the literature on student organizational conflict and offers practical insights for managing internal organizational conflicts based on values and formal rules. Conclusion: Structural intervention through the appointment of an Acting Leader serves as an effective mechanism for conflict resolution in student organizations, although its long-term success depends on the ability to rebuild trust and consolidate organizational vision. Strengthening communication mechanisms and internalizing organizational values are essential for preventing similar conflicts in the future.